(untitled) (Chittagong University Journal of Biological Sciences, 2024)
A critical examination and identification of the specimens of the family Orchidaceae collected from the south-eastern part of Bangladesh resulted in to new records,viz. AeridesroseumLoddiges. ex. Lindl. and Bulbophyllumcylindraceum Wall. ex. Lindl.for Bangladesh. In the present communication, detailed descriptions with photographs, flowering time,ecology, and geographical distribution of the species have been provided. The Chittagong Univ. J. B. Sci. 9(1&2):119-124,2019